Efficient defect healing and ultralow sheet resistance of laser-assisted reduced graphene oxide at ambient conditions. (November 2018) - Antonelou, Aspasia; Sygellou, Labrini; Vrettos, Katerina; Georgakilas, Vasilios; Yannopoulos, Spyros N.
Abstract: Reduction of graphene oxide (GO) to a low-resistance product is one of the most versatile routes to obtain large volume graphene-based materials. A number of chemical and thermal methods are being applied to achieve this goal, albeit each one is bound to certain disadvantages and limitations. Laser-assisted reduction has emerged as a promising method apt to overcome issues related to chemical and thermal reduction. Despite that a large number of efforts have been focused on laser-induced reduction of GO, its transformation to high quality reduced GO still remains a bottleneck. Here, it is shown that low-cost, millisecond lasers, widely used in the welding industry, achieve excellent reduction of GO to a product with the lowest sheet resistance yet reported by any laser-assisted method. For comparison, GO is reduced by chemical and thermal methods. Raman and x-ray photoelectron spectroscopies are applied to investigate the underlying structural changes providing evidence for the removal of oxygen-containing species and defect healing. Operation at ambient conditions, single pulse irradiation and a 2.60 mm wide focusing spot, demonstrate the high potential of this approach to the scalability of the reduction process towards producing large volumes of high-quality reduced graphene oxide at low cost. Graphical abstract: Image 1